Pre-oxidation and adsorption with powdered activated carbon for taste and odor control and optimizing coagulation for dissolved organic carbon removal - Vundala, Janardhan, author; Carlson, Kenneth, advisor; Catton, Kimberly, committee member; Bradley, Thomas, committee member (Colorado State University. Libraries, 2018)
Geosmin and MIB (2-Methylisoborneol) are the two natural organic compounds produced by certain types of blue-green algae which cause taste and odor (T&O) issues in the sources of drinking water. Geosmin and MIB are not regulated by United States Environmental Protection Agency (USEPA) as they do not pose a health risk, but these two organic compounds seriously hinder the aesthetic appeal of finished drinking water due to the earthy or musty odor produced by them even at very lower concentrations (below 10 ng/L). Geosmin and MIB cannot be eliminated by conventional drinking water treatment processes, hence more advanced treatment techniques involving an adsorption agent like Powdered Activated Carbon (PAC) is necessary to remove these odorants and achieve concentration below the odor threshold. Boyd Lake Water Treatment Plant in Greeley region, gets it intake of raw water from two main drinking waters sources namely Boyd Lake and Lake Loveland. The plant has been experiencing T&O related issues mostly during the mid-summer to late autumn. This study was conducted for BLWTP in three phases to determine the optimal conditions to address the seasonal T&O issue and also help reduce the Dissolved Organic Carbon (DOC) content of the source waters efficiently with PAC. Preliminary testing was conducted on Lake Loveland and Boyd Lake water with an incremental alum dosage from 30 to 70 mg/L followed by three five minute stages of flocculation and 45 minutes settling time. Turbidity, TOC and DOC were measured before and after coagulant testing. The results indicated that Boyd Lake water was the hardest to treat, hence it was selected for further testing. In the initial phase of the study, about ten different PACs were tested in five batches, with Boyd Lake and plant mix water collected at different time periods. The results from the five batches were averaged and ranked based on the DOC reduction values. The results indicated that PAC Hydrodarco M was the cost and performance wise effective of the ten PACs tested. The second phase of the study involved testing four different PACs at four different contact times (15, 30, 45 and 60 minutes) with one constant dosage of 30mg/L for the kinetic study part. The results showed that maximum DOC removal was achieved at 45 minutes contact time. Similarly, the same four different PACs were tested with four PAC doses (10, 20, 30 and 40 mg/L) with one preset contact time of 45 minutes for the dosage study part. The results from these tests indicated that 30 mg/L was the optimal PAC dosage for maximum DOC removal. In the final phase, the raw water was initially treated with the various pre-oxidants with dosages of 1mg/L ClO2, 5 and 10 mg/L of NaMnO4 with a contact time of 60 seconds followed by PAC treatment with a dosage of 30 mg/L and a 45 minutes contact time. Test results revealed that pre-oxidants did not have a significant impact in DOC removal at any dosage levels. Additionally, two dosages 20 and 70 mg/L of coagulant alum were tested with pre-oxidant and PAC treated water. Detailed analysis was performed with coagulant alum in combination with pre-oxidant and PAC treated water. The results of the alum testing illustrated that a higher dosage of coagulant alum at 70 mg/L had a substantial effect on the DOC removal when compared to a lower dosage of 20 mg/L. Further, the results showed a two-fold increase in the DOC reduction at an alum dosage of 70 mg/L without the presence of any pre-oxidants.